The Black Bruins : the remarkable lives of UCLA's Jackie Robinson, Woody Strode, Tom Bradley, Kenny Washington, and Ray Bartlett - Johnson, James W., 1938- (University of Nebraska Press, 2017)
"The intertwined story of five influential African American athletes who came together as teammates at UCLA in the 1930s"--